Uso de óleos essenciais, extratos vegetais e indutores de resistência no controle alternativo do mal-do-Panamá da bananeira - Silva, Julio Cesar da (2007)
The banana tree (Musa spp.), is a plant explored in the majority of the tropical countries. Its fruit is consumed in practically all the countries of the world "in nature" or in form of candies, compotes, tinned, flakes, etc., which had to its energy value, caloric and wealth in vitamins and leaves minerals. The banana tree can be attacked by some pathogen, being distinguished fungus Fusarium oxysporum f. sp. cubense (Foc) that cause Panama disease, one of the main diseases of the culture. The search for alternative methods of control has been searched and in special the use of essential oils and vegetables extracts. This work was developed in laboratory conditions and greenhouse of the CECA/UFAL, with objectives to evaluate the fungitoxici effect "in vitro", "in vivo" and as inductive resistance of essential oils of Eucalyptus spp. (eucalypt citriodora variety), Cymbopogon winteranus (citronella), Caryophyllus aromaticus L. (india crave) and Piper aduncum L. (pepper-of-monkey) and of watery vegetables extracts of Caryophyllus aromaticus L. (india crave), Cinnamomum zeylanicum (cinnamon), Allium sativum L. (garlic), Ocimum basilicum (basil), Zingiber officinale Rosc. (ginger) and Ruta graveolens (arruda) and of the commercial products the ASM and Ecolife®. The oils had been added to the way of BDA in the 1,25 concentrations; 2,5; 3,75 and 5% and the watery vegetables extracts had been added to the way of BDA, in the concentrations of 5; 10; 15 and 20 % for watery vegetables extracts and 0,25; 0,5; 0,75 and 1 % for Ecolife®. For evaluation the index of intensity of the disease (ID), spread plants of banana tree of the variety apple had been sprayed with essential oils (1,25%) and with extracts of garlic and cinnamon (20%), extract of crave (15%) and Ecolife® (0,75%).After, the plants had been eight days inoculated with the suspension of Foc (104 con.mL-1), for the method of immersion of roots, for one hour. The oil of citronella, eucalypt, in all the tested concentrations, and the extracts of crave (15 and 20%) and Ecolife® (0,75 and 1%) had inhibited in 100% the mycelial growth of fungus, thus constituting the best treatments. While that, the oils of crave and pepper-of-monkey and the extracts of garlic and cinnamon had inhibited the mycelial growth partially, in all the tested concentrations, being that the extract of garlic to the measure that increased the concentration showed an increment in the PIC of fungus. In the in vivo evaluation, the oil of citronella presented the best one resulted (ID=25%), differing from the witness, the oils of crave and of eucalypt ID had presented = 95 and 75%, respectively. The extracts of crave and garlic, and Ecolife® ID had presented = 29, 25 and 8,33%. The total or partial inhibition of the mycelial growth of F. oxysporum f. sp. cubense, evaluated "in vivo", for essential oils and watery vegetables extracts, in the sample composites of antifúngica action. The activities of the phenylalanine enzyme ammonia lyase (PAL) were determined in plants submitted to the treatments, collected to the 24, 48, 72, 144 and 288 hours after the inoculation. Significant difference between the inductors and the witness, being distinguished Ecolife®, extract of basil was observed, oil of citronella, oil and extract of crave, and extract of arruda that had provided to the lesser indices of disease in the apple banana changes, respectively with 8,33; 12,5; 25,0; 29,17; 25,0; e 41,67 %.The Ecolife® inductor presented the best performance in relation to the other tested inductors and the witness, providing a control of 83,7% of the disease. All the analyzed treatments had presented the presence of the enzyme in accordance with, varying the level the date of extraction and the extract or used oil as inductive of resistance. The extract of crave presented one high enzymatic activity in extraction 24 and 48 hours after the inoculation of inoculate it.